(untitled) (Journal of the College of Education for Women, 2019)
In this paper, an algorithm through which we can embed more data than theregular methods under spatial domain is introduced. We compressed the secret datausing Huffman coding and then this compressed data is embedded using laplaciansharpening method.We used Laplace filters to determine the effective hiding places, then based onthreshold value we found the places with the highest values acquired from these filtersfor embedding the watermark. In this work our aim is increasing the capacity ofinformation which is to be embedded by using Huffman code and at the same timeincreasing the security of the algorithm by hiding data in the places that have highestvalues of edges and less noticeable.The performance of the proposed algorithm is evaluated using detectiontechniques such as Peak Signal- to- Noise Ratio (PSNR) to measure the distortion,Similarity Correlation between the cover-image and watermarked image, and BitError Rate (BER) is used to measure the robustness. The sensitivity against attacks onthe watermarked image is investigated. The types of attacks applied are: Laplaciansharpening, Median filtering, Salt & Peppers Noise and Rotating attack. The resultsshow that the proposed algorithm can resist Laplacain sharpening with any sharpeningparameter k, besides laplacian good result according to some other types of attacks isachieved.